A Pathology-Based Combined Model to Identify PAM50 Non-luminal Intrinsic Disease in Hormone Receptor-Positive HER2-Negative Breast Cancer - Pascual, Tomás; Martin, Miguel; Fernández-Martínez, Aranzazu; Paré, Laia; Alba, Emilio; Rodríguez-Lescure, Álvaro; Perrone, Giuseppe; Cortés, Javier; Morales, Serafín; Lluch, Ana; Urruticoechea, Ander; González-Farré, Blanca; et al. (Frontiers in Oncology, 2019)
Background: In hormone receptor-positive (HR+)/HER2-negative breast cancer, the HER2-enriched and Basal-like intrinsic subtypes are associated with poor outcome, low response to anti-estrogen therapy and high response to chemotherapy. To date, no validated biomarker exists to identify both molecular entities other than gene expression. Methods: PAM50 subtyping and immunohistochemical data were obtained from 8 independent studies of 1,416 HR+/HER2-negative early breast tumors. A non-luminal disease score (NOLUS) from 0 to 100, based on percentage of estrogen receptor (ER), progesterone receptor (PR) and Ki67 tumor cells, was derived in a combined cohort of 5 studies (training dataset) and tested in a combined cohort of 3 studies. The performance of NOLUS was estimated using Area Under the ROC Curve (AUC). Results: In the training dataset (n=903) and compared to luminal disease, non-luminal disease had lower percentage of ER-positive cells (median 65.2% vs 86.2%, p<0.01) and PR-positive cells (33.2% vs 56.4%, p<0.01) and higher percentage of Ki67-positive cells (18.2% vs 13.1%, p=0.01). A NOLUS formula was derived: -0.45*ER -0.28*PR +0.27*Ki67 + 73.02. The proportion of non-luminal tumors in NOLUS+ and NOLUS-negative groups was 52.6% and 8.7%, respectively. In the testing dataset (n=514), NOLUS was found significantly associated with non-luminal disease (p<0.01) with an AUC 0.902. The proportion of non-luminal tumors in NOLUS+ and NOLUS-negative groups was 76.9% (56.4-91.0%) and 2.6% (1.4-4.5%), respectively. The sensitivity and specificity of the pre-specified cutoff was 59.3% and 98.7%, respectively. Conclusions: In the absence of gene expression data, NOLUS can help identify non-luminal disease within HR+/HER2-negative breast cancer.